Ionic Modulation at the LaAlO3/KTaO3 Interface for Extreme High‐Mobility Two‐Dimensional Electron Gas. Issue 35 (20th October 2022) - Yan, Hong; Zeng, Shengwei; Rubi, Km; Omar, Ganesh Ji; Zhang, Zhaoting; Goiran, Michel; Escoffier, Walter; Ariando, Ariando
Abstract: Due to the coexistence of many emergent phenomena, including 2D superconductivity and a large Rashba spin‐orbit coupling, 5d transition metal oxides‐based two‐dimensional electron systems (2DESs) have been prospected as one of the potential intrants for modern electronics. However, despite the lighter electron mass, the mobility of carriers, a key requisite for high‐performance devices, in 5d‐oxides devices remains far behind their 3d‐oxides analogs. The carriers' mobility in these oxides is significantly hampered by the inevitable presence of defects. Here, very high mobility (≈22 650 cm 2 V −1 s −1 ) of 5d‐2DES confined at the LaAlO3 /KTaO3 interface is reported. The high mobility, which is beyond the values observed in SrTiO3 2DESs in the same carrier‐density range, is achieved using the ionic‐liquid gating at room temperature. The authors postulate that the ionic‐liquid gating affects the oxygen vacancies and efficiently reduces any disorder at the interface. Investigating density and mobility in a broad range of back‐gate voltage, the authors reveal that the mobility follows the power‐law µ ∝ n 1.2, indicating the very high quality of ionic‐liquid‐gated LaAlO3 /KTaO3 devices, consistent with the postulate. Furthermore, the analysis of the quantum oscillations confirms that the high‐mobility electrons occupy the electronic sub‐bands emerging from the Ta:5d orbitals of KTaO3 . Abstract : The carriers' mobility in 5d transition metal oxides‐based two‐dimensional electron systems is significantly hampered by the inevitable presence of defects. In order to overcome this challenge, ionic‐liquid gating at room temperature is applied to affect the oxygen vacancies and efficiently reduce any disorder at the interface. In this way, very high mobility of the amorphous LaAlO3 /KTaO3 interface is demonstrated.